2006
DOI: 10.1242/jcs.03208
|View full text |Cite
|
Sign up to set email alerts
|

Gliotactin and Discs large form a protein complex at the tricellular junction of polarized epithelial cells inDrosophila

Abstract: The tricellular junction (TCJ) forms at the convergence of pleated septate junctions (SJs) from three adjacent cells in polarized epithelia and is necessary for maintaining the transepithelial barrier. In Drosophila, the transmembrane protein Gliotactin was the first identified marker of the TCJ, but little is known about other molecular constituents. We now show that Gliotactin associates with Discs large at the TCJ in a Ca2+-dependent manner. Discs large is essential for the formation of the TCJ and the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 44 publications
3
41
0
Order By: Relevance
“…We hypothesized that Gli would localize to the TCJ complex in the epithelia of larval mosquito, as has previously been reported in D. melanogaster (see Schulte et al, 2003Schulte et al, , 2006; however, this was not the case as in most tissues examined, Gli localized at bicellular SJs. In contrast, the hypothesis that Gli expression would respond to alterations in salinity can be accepted as Gli levels were found to exhibit an organ-specific increase in animals reared in BW.…”
Section: Discussion Overviewmentioning
confidence: 64%
See 4 more Smart Citations
“…We hypothesized that Gli would localize to the TCJ complex in the epithelia of larval mosquito, as has previously been reported in D. melanogaster (see Schulte et al, 2003Schulte et al, , 2006; however, this was not the case as in most tissues examined, Gli localized at bicellular SJs. In contrast, the hypothesis that Gli expression would respond to alterations in salinity can be accepted as Gli levels were found to exhibit an organ-specific increase in animals reared in BW.…”
Section: Discussion Overviewmentioning
confidence: 64%
“…The vertebrate homologs of Gli, neuroligins, have been shown to dimerize or oligomerize via their extracellular serine esterase-like domain (Ichtchenko et al, 1995(Ichtchenko et al, , 1996, and Gli dimerization has also been suggested for D. melanogaster (Venema et al, 2004;PadashBarmchi et al, 2013). In contrast, we can not rule out the possibility that the observed ∼245 kDa Gli band may be a product of a Gli heterodimer complex with another SJ protein such as Dlg, which has been shown to occur in adult D. melanogaster (Schulte et al, 2006).…”
Section: Gli Expression and Localization In The Osmoregulatory Organsmentioning
confidence: 64%
See 3 more Smart Citations